Estudos sobre a produção biogênica de metano em sedimento marinho próximo à Geleira Wanda, Ilha Rei George, Península Antártica - Rafael, Laissa Soares [UNIFESP] (2018)
Methanogenisis occurs in many antarctic ecosystems. In marine sediments, the presence of methylated compound derived of osmolytes can be a source of methanogenic substrates. In the Antarctic Peninsula, glaciers have been retreating due climate change, exposing the soil and modifying the nutrient circulation dynamics, also impacting the microbial ecology in its environment. The purpose of the present work was to study the cultivable diversity of methylotrophic methanogens from marine sediment collected on the vicinity of Wanda Glacier. Enrichment culture were made in artificial seawater media with different final concentration of trimethylamine (TMA) and methanol, under H2:CO2 ou N2:CO2 atmosphere at 20ºC,cultures were monitored for methane production by gas chromatography (GC), cell morphology described by phase contrast and fluorescence microscopy and taxonomic composition was investigated through Illumina MiSeq sequencing. Colonies were obtained through toll-tube. Cultures with TMA produced more methane in a short period of incubation. In some cultures methane production was higher in the presence of hydrogen. The methanogenic genus Methanococcoides and Methanosarcina were observed in cultures, there was a predominance of Methanosarcina in cultures under hydrogen atmosphere.. Sequencing of bacteria from the genera Sedimentibacter, Desulfoconvexum, Desulfobacterium and Desulfobacula, besides uncultured bacterial genera. In roll-tube the genus Actinotalea e Rhodanobacter were predominant, but it wasn’t possible to obtain isolates. It was concluded that the strategy used to enrich methylotrophic methanogenic archaea was successful and it was also possible to observe differences in methane production and in the composition of the communities according to the substrates used. The roll-tube technique was not efficient for the isolation of cultures of methanogenic archaea, adaptations will be necessary. The results indicate that methylotrophic metabolism is important in Antarctic marine sediments, possibly due to the availability of substrates in marine environments and non-competitiveness with sulfate reducing bacteria.